2011
DOI: 10.1289/ehp.1002701
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Urinary Concentrations of Bisphenol A in Spot Samples, First Morning Voids, and 24-Hour Collections

Abstract: Background: Human exposure to bisphenol A (BPA) is widespread. After exposure, BPA is rapidly metabolized and eliminated in urine. Therefore, there is considerable within-person and between-person variability of BPA concentrations in spot urine samples. However, no information exists on the within-day variability of urinary BPA concentrations.Objectives: We examined the between-person and within-person and between-day and within-day variability in the urinary BPA concentrations of eight adults who collected al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
177
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 272 publications
(188 citation statements)
references
References 33 publications
8
177
1
2
Order By: Relevance
“…22,47,49,50 With the assumption of nondifferential exposure misclassification, this error would result in null-biased estimates. 51 Integrated exposure measures such as mean BPA concentrations might reduce misclassification rates, but they would decrease the ability to identify short timesensitive windows of development.…”
Section: Figurementioning
confidence: 99%
“…22,47,49,50 With the assumption of nondifferential exposure misclassification, this error would result in null-biased estimates. 51 Integrated exposure measures such as mean BPA concentrations might reduce misclassification rates, but they would decrease the ability to identify short timesensitive windows of development.…”
Section: Figurementioning
confidence: 99%
“…Second, single spot urine measures may not be representative of long-term exposure to BPA. Considerable within-person variability has been shown in urinary BPA measured throughout the day and week 47 and over a period of 1 to 3 years, 48 likely relating to variations in dietary intake. However, our sensitivity analyses showed that time of urine collection and fasting status did not confound the associations observed.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…7,8,10 The CDC data set was generated from a 1-week urine collection effort. Briefly, eight volunteers (4 men and 4 women) collected each urinary void over the course of a week, recording the time and volume of each void before preserving an aliquot for analysis.…”
Section: Data Sets For Evaluation Of Urinary Simulation Predictionsmentioning
confidence: 99%
“…The results of the simulations are compared with data collected and recently published by researchers from the Centers for Disease Control and Prevention (CDC) in an observational study of eight volunteers who collected each urine void for a week 7,8,10 and are used to examine population data from the National Health and Nutrition Examination Survey (NHANES). The simulations and data sets allow examination of the impact of within-day temporal variability on how representative spot sample biomarker concentrations are of longer-term biomarker concentrations and underlying exposure levels.…”
mentioning
confidence: 99%